Chemical analyses of the major ions in the precipitation of Istanbul, Turkey - (:unkn) unknown (ELSEVIER SCI LTD, 1999)
The issue of acid deposition and associated environmental problems has received spescial attention during recent decades and has been the subject of extensive research in North America and Western Europe. However, similar studies in developing countries are very limited due to technological and financial restrictions. In this study, chemical composition of the precipitation in istanbul was investigated. Precipitation samples were obtained from three urban areas Bahcelievler, Florya, and Goztepe for the period of January to October 1996. In the initial phase of the study (January to April 1996), samples were analyzed for hydrogen, sulfate and nitrate ions, and in the final phase (May to October 1996) calcium, bicarbonate and ammonium ions were included in the measurement program. The effect of the urban heating demand on the chemical composition of the precipitation was observed clearly. During the heating season (December to March period), sulfate and nitrate concentrations in the precipitation were very high; sulfate fluctuating between 0 and 150 mg/litre and nitrate between 0 and 70 mg/litre. On the other hand, they dropped to very low levels during the April to October period when the urban heating demand decreases or ceases. High pH Values associated with high sulfate and high nitrate concentrations reveal that the acidity of the precipitation is neutralized. Correlations between calcium and sulfate, and ammonium and sulfate imply that CaSO4 and (NH4)(2)SO4 aerosols may merge with the precipitation, and neutralize the acidity. (C) 1999 Published by Elsevier Science Ltd. All rights reserved.
Keywords: acid precipitation; neutralizing agents; air pollution; ACID-RAIN; WET DEPOSITION; CLIMATE-CHANGE; URBANIZATION; CHEMISTRY